Decoupled power control for direct-modulation-based modular multilevel converter with improved stability - Wang, Jinyu (2021)
Direct modulation principle is widely used in modular multilevel converters (MMCs) for its simplicity and natural stability. However, it results in strong active and reactive power coupling. This paper carefully analyzes and identifies four power coupling paths and two power influence factors with the direct modulation principle. Full power decoupling of the MMC can be realized by cutting off the derived coupling paths and compensating the influence factors. However, this will further deteriorate the already poor damping of the MMC and significantly increase dc-bus current fluctuations. To solve this problem, the sources resulting in poor damping are identified and then a new closed-loop dc-bus current controller is incorporated into the control system. Finally, the proposed power decoupling strategy with the newly designed current controller realizes completely decoupled power regulation, avoids overload operation, and obviously improves the dynamic performance of the MMC. Furthermore, it increases the stability of the MMC system under all possible operation conditions. The proposed control strategy is confirmed by experimental results.